2001
DOI: 10.1080/03610730109342352
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cognitive Ability in Normotensive and Hypertensive 68-Year-Old Men: Results from Population Study “Men Born in 1914,” in Malmö, Sweden

Abstract: Hypertension and its consequences on cognition was analyzed using data from the study "Men born in 1914" in Malmö, Sweden, a prospective cohort study of cardiovascular disease. The baseline examinations took place in 1982/83 where 500 men participated in extensive medical and social examinations. A neuropsychological investigation was completed including five standardized cognitive tests. The specific purpose of the study was to investigate whether hypertension was associated with cognitive performance. By the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…Elevated diastolic blood pressure [57] or high general blood pressure [63,73,82,86] were associated with poor linguistic performance. However, two studies [65,70] showed that poor linguistic performance was related to low blood pressure.…”
Section: Blood Pressure and Languagementioning
confidence: 99%
See 1 more Smart Citation
“…Elevated diastolic blood pressure [57] or high general blood pressure [63,73,82,86] were associated with poor linguistic performance. However, two studies [65,70] showed that poor linguistic performance was related to low blood pressure.…”
Section: Blood Pressure and Languagementioning
confidence: 99%
“…Eleven studies [75,[80][81][82][83][85][86][87][88][89][90] made a comparison between hypertensive and normotensive individuals. According to the international guidelines [91,92].…”
Section: Blood Pressure Measurementsmentioning
confidence: 99%
“…Researchers focusing on the cognitive effects of controlled and uncontrolled hypertension have also shown associations between deficits in both verbal (Elias et al, 1993; Waldstein et al, 1991) and nonverbal memory (André-Petersson, Hagberg, Janzon, & Steen, 2001; Harrington et al, 2000; Swan et al, 1998) and high blood pressure in both groups. This suggests that controlled hypertension can also be associated with cognitive changes in older adults, although the extent of deficits may not be as pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…destacam-se os prejuízos de memória, processamento das informações e velocidade de resposta (Harrington et al, 2000;Almeida e Flicker, 2001;Andre-Petersson et al, 2001;Asimakopoulou et al, 2002;Bennett et al, 2003;Antonelli Incalzi et al, 2003). A partir da classificação da gravidade de ICC de acordo com os critérios da New York Heart Association (NYHA), o comprometimento da memória, em especial de fixação e aprendizado (Harrington et al, 2000), nos pacientes com ICC nas classes funcionais (CF) I, II e III da NYHA vem sendo apontado consistentemente na literatura (Deary et al, 1991;Grubb et al, 2000;Glynn et al, 2002;Elias et al, 2003;Bennett e Sauve, 2003;Antonelli Incalzi et al, 2003).…”
Section: Introductionunclassified